Securing the Enterprise: How Dynamics 365 Meets Global Compliance Standards - Muppaneni, Rajarshi Krishna (International Journal of Emerging Research in Engineering and Technology, 2021)
Businesses the present day are under increasing demands to keep data private, follow the rules & keep their operations safe all over the globe. Microsoft Dynamics 365 has become a strong business platform that meets these needs effectively with important global adherence to rules including GDPR, HIPAA, ISO 27001 & FedRAMP. This study analyzes how Dynamics 365 enables the Integration of compliance into necessary business functions via data governance, automated threat detection & transparent simple adherence reports. The study utilizes a multi-method approach, including a literature analysis, an applied compliance framework, and a practical case study, to analyze the platform’s technical and procedural safeguards. The findings demonstrate that Dynamics 365’s integrated data model, role-specific access controls, audit trails, and cloud security certifications substantially improve organizational resilience and ensure adherence to multi-jurisdictional requirements. The report also emphasizes the significance of Computerization & AI in reducing human mistake & ensuring that their regulatory compliance via vigilant monitoring & policy implementation. Ultimately, Dynamics 365 demonstrates that compliance can transition from a Vigilant control to a proactive & competitive advantage. This helps organizations not only protect their information, but also develop trust, transparency & process improvement in a regulatory climate that changes extremely rapidly.